PELATIHAN KOMPUTER DASAR TERHADAP KEMAMPUAN PENDIDIK PAUD DALAM PEMANFAATAN TIK: Basic Computer Training on the Ability of PAUD Educators in Utilizing ICT - Alfannisa Fajrin; Tukino Tukino; Erlin Elisa (PUAN INDONESIA, 2023)
Obstacles to the use of ICT by PAUD educators are lack of access to ICT skills development, lack of knowledge about ICT, and lack of willingness of educators to utilize ICT. Knowing these conditions, Putera Batam University Lecturers took the initiative to organize a basic computer training program based on identifying the needs of PAUD educators in the area. The acceleration and expansion of Early Childhood Education (PAUD) services is one of the strategic policies rolled out by the Ministry of National Education. One of the strategies to improve the quality of PAUD educators that has been implemented so far is through the development of clusters. Microsoft Office application or better known as Office, of course almost everyone knows it, especially for those who usually deal with writing or reports. Members of the PAUD Cluster Work Center are no exception. For members of the PAUD Cluster Working Center, Microsoft Office 2019 is of course very helpful in their activities in preparing learning, carrying out learning activities, up to the evaluation and reporting stages of activities carried out.